Cirurgia da fibrilação atrial crônica com ultrassom em pacientes com lesão valvar mitral - Brick, Alexandre Visconti (2016)
Introduction: Atrial fibrillation (AF) is the most common arrhythmia with high morbidity and mortality rates. The use of catheter ablation for treatment of AF has stimulated the use of energy sources such as ultrasound (US) in surgery to cause injuries in endocardial way, epicardial way or both, replacing the section and suture of the atrial wall. The presence of previous heart disease, most often injury of the mitral valve in patients with chronic atrial fibrillation (CAF) justifies the surgical treatment of this arrhythmia concomitant to the valve surgery. Objective: To evaluate surgical treatment of CAF with US in patients with mitral valve disease, considering: 1- Preoperative clinical characteristics of patients undergoing surgical treatment of CAF and 2- Follow up of patients in the immediate postoperative period, in hospital and later high up to 60 months. Patients and Method: We retrospectively and consecutively studied 100 patients with CAF and mitral valve disease who underwent surgical treatment using US ablation, aged between 18 and 70 years (43.56 ± 4,94 anos), 63 (63%) were female and 37 (37%) were male. Patient data were reviewed prospectively by consulting the control reports, including demographic variables (gender and age) and heart [signs and symptoms, underlying disease, functional class, hospital stay, surgical procedure time, ablation time, intraoperative and postoperative (immediately discharged and later up to 60 months)]. It was used the actuarial curve (Kaplan-Meier) for the study of permanence without recurrence after 12, 24, 36, 48 and 60 months in patients with CAF. Results: From the patients studied, 86% had rheumatic mitral valve disease, 14% degeneration of the mitral valve, 40% were patients with mitral regurgitation, 19% of mitral lesion, 36% of mitral stenosis and 5% of mitral restenosis. The main symptoms included palpitations related to tachycardia by CAF (70%), congestive heart failure (70%), previous episodes of acute pulmonary edema (27%), stroke by thromboembolism accident (13%) and peripheral embolism (7%). The functional class of patients was III/IV. The early results showed that 94% of patients undergoing ablation US reversed the rate of CAF, being 86% in sinus rhythm and 8% in atrioventricular block, which was transient. At hospital discharge was observed maintenance of sinus rhythm in 86% of patients and recurrence of CAF in 8%. At follow-up after 60 months 83.8% of patients maintained the sinus rhythm. Conclusions: Patients with rheumatic mitral valve disease often have failure and mitral stenosis, palpitations related to tachycardia by CAF and congestive heart failure. Surgical treatment of CAF with US concomitant to the mitral valve surgery is feasible and satisfactory, with maintenance of sinus rhythm in most patients (83.8%) after 60 months of follow-up.